2021
DOI: 10.17221/123/2020-pps
|View full text |Cite
|
Sign up to set email alerts
|

Erwinia mallotivora is the causal agent of papaya bacterial crown rot disease in Lampung Timur, Indonesia

Abstract: Sixteen bacterial strains showing oval, convex with a white colony colour were obtained from the water-soaked lesions on the petioles and leaves of infected papaya (cv. calina) collected from a papaya field in Lampung Timur, Indonesia. The pathogenicity test showed that all the strains produced the same symptoms with those found in the field. Four representative strains were then chosen for further investigation. The phenotypic characteristics revealed that the strains resembled Erwinia mallotivora. Two repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…For example Pectobacterium subsp. brasiliensis ( Moleleki et al, 2013 ) which is recently named as P. brasiliense ( Portier et al, 2019 ) and Erwinia mallotivora ( Suharjo et al, 2021 ) revealed positive result on tobacco hypersensitive reaction test, however some of pectobacterium species i.e. P. atrosepticum and P. wasabiae type strain (isolated from wasabi) as well as P. wasabiae isolated from potato which is currently known as P. parmentieri ( Khayi et al, 2016 ) produced negative result ( Kim et al, 2009 ; Moleleki et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example Pectobacterium subsp. brasiliensis ( Moleleki et al, 2013 ) which is recently named as P. brasiliense ( Portier et al, 2019 ) and Erwinia mallotivora ( Suharjo et al, 2021 ) revealed positive result on tobacco hypersensitive reaction test, however some of pectobacterium species i.e. P. atrosepticum and P. wasabiae type strain (isolated from wasabi) as well as P. wasabiae isolated from potato which is currently known as P. parmentieri ( Khayi et al, 2016 ) produced negative result ( Kim et al, 2009 ; Moleleki et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, farmers rely on preventive measures and good management practices to contain and minimise the spread of the disease to neighbouring trees and plots [ 5 , 10 , 11 ]. Recently, E. mallotivora was reported to be affecting papaya in the Philippines and Indonesia, making this species a pathogen of concern that could affect the papaya industry in the entire Southeast Asia region [ 7 , 12 ]. A similar disease termed as papaya black rot has been recently detected in Japan and the pathogen was characterised to be from the genus Erwinia [ 13 ].…”
Section: Introductionmentioning
confidence: 99%